2003
DOI: 10.1081/lft-120024558
|View full text |Cite
|
Sign up to set email alerts
|

Preparative Subfractionation of Petroleum Resins and Asphaltenes. II. Characterization of Size Exclusion Chromatography Isolated Fractions

Abstract: In the first study of this series, resins and asphaltenes from stable and unstable crude oils have been separated by size exclusion chromatography in three molecular mass ranges (MM: high, medium, and low). In the present study, the isolated fractions were further characterized in order to correlate several of their structural properties with crude oil tendency to solid deposition. Elemental analysis (C, H, S, N), infrared spectrophotometry (IR), and proton nuclear magnetic resonance ( 1 H NMR) were the charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…32 SEC preparative separation of asphaltenes showed that the eluates of higher apparent MW were the most aggregative fractions, possessing the higher contents of heteroatoms and lower H/C ratios. 33,34 The Canadian province of Alberta possesses one of the most abundant bitumen reserves worldwide, thus, surplus of asphaltenes from upgrading processes is a fact affecting the province from the environmental and economic points of view. Among feasible ways under study for asphaltenes valorization, oxidative reactions 35 and/or nanocatalytic asphaltene hydroprocessing 36 are underway; thus, requiring substantial amounts of asphaltene feedstocks to carry out the studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 SEC preparative separation of asphaltenes showed that the eluates of higher apparent MW were the most aggregative fractions, possessing the higher contents of heteroatoms and lower H/C ratios. 33,34 The Canadian province of Alberta possesses one of the most abundant bitumen reserves worldwide, thus, surplus of asphaltenes from upgrading processes is a fact affecting the province from the environmental and economic points of view. Among feasible ways under study for asphaltenes valorization, oxidative reactions 35 and/or nanocatalytic asphaltene hydroprocessing 36 are underway; thus, requiring substantial amounts of asphaltene feedstocks to carry out the studies.…”
Section: Introductionmentioning
confidence: 99%
“…aggregation phenomena have been studied relying on SEC literature,23,25,26,31,33,34,46,47 being re-aggregation phenomena of low MW pre-separated fractions toward high MW entities that eluted at higher apparent MWs, reported before 33. …”
mentioning
confidence: 99%
“…There are many studies in the open literature dealing with sampling and identification of many different compounds present in those fractions and the changes that they undergo when submitted to different treatments and solvent extraction procedures. Thus far, many families of compounds have been identified by diverse techniques involving solvent extraction procedures, fractionation, and reactions and their subsequent identification by many analytical techniques: gas chromatography–mass spectrometry (GC-MS), size exclusion chromatography, and NMR or by direct measurement using spectroscopy techniques, such as infrared (IR), , X-ray absorption near-edge spectroscopy (XANES), near-UV/visible absorption spectroscopy, time-of-flight secondary-ion mass spectrometry (TOF-SIMS), , Auger electron spectroscopy, and X-ray photoelectron spectroscopy (XPS), although with a limited scope and some of them with errors . Many of these techniques have been discussed in more detail by Merdrignac and Espinat .…”
Section: Introductionmentioning
confidence: 99%
“…Band near 1030 cm −1 can be related to ester linkages or sulfoxides (Wilt et al 1998). Band near 1260 cm −1 can be attributed to groups containing singly bonded oxygen, e.g., esters or ethers (Carbognani and Espidel 2003). The distinct band observed at 1600 cm −1 is related to the aromatic C=C-stretching vibrations.…”
Section: Quality Assurance Of Datamentioning
confidence: 99%